Human spaceflight - Furgang, Adam (From Earth to the stars., 2018)
Explores the history of manned spaceflight, discussing the US space program, the effect of outer space on the human body, what it takes to become an astronaut, and the future of human spaceflight. Includes sidebars, a glossary, and resources for further information.